Implementation research in Primary Care (Part 1): What is implementation research? - Ooi, Chor Yau; Tong, Wen Ting; Anne, Sales; Ng, Chirk Jenn (Academy of Family Physicians of Malaysia (AFPM), 2026)
Implementation research plays a vital role in narrowing the “evidence-to-practice” gap in primary care by ensuring that evidence-based interventions are not only adopted but also embedded into routine clinical practice in a sustainable way. This is especially important in primary care, where clinicians care for diverse patient groups, work within evolving healthcare systems, and face rapid technological change. Implementation research is defined as “the scientific study of methods to promote the systematic uptake of research findings and other evidence-based practices into routine practice, thereby improving the quality and effectiveness of health services.” This commentary introduces the concept and significance of implementation research, outlines its place within the broader research translation continuum, and clarifies how it differs from quality improvement. It also provides examples of how implementation research is applied in primary care to support the adoption of new innovations.should be further verified.